Politik Uang Sebagai Upaya Mendapatkan Suara Masyarakat Perspektif Hukum Islam - Zulhendra, Joni; AS, Boiziardi (Fakultas Hukum Universitas Tamansiswa Padang, 2023)
This article is motivated by the phenomenon in society of using money as an effort to get people's votes in elections. In the perspective of Islamic law, money politics is called risywah or bribery, an act that is false or counteracts a rightful act and is prohibited by the syara' because it can damage the government structure. In Islamic law and in law, money politics is viewed as a prohibited act and as a result of this act the perpetrator can be punished by a judge in accordance with the applicable law, whereas in Islamic law a person who has been given the mandate to become a leader, then he or she cannot If you care for it well, a person will not smell the smell of heaven. The difference between the two views of money politics is not too explicit, namely that the source of Islamic law comes from the Koran and hadith, while laws originate from humans or regulations are made by humans